Jesus, Inc. : the visionary path : an entrepreneur's guide to true success - Jones, Laurie Beth. (New York : Crown Business, 2001)
Publisher Fact Sheet Six years ago, Laurie Beth Jones offered an irresistible motivational proposition in Jesus, CEO: If Jesus could change the world with a team of just 12 men, shouldn't He have something to teach each of us about managing our teams? Readers were intrigued enough to make the book a New York Times best-seller. Now, in Jesus, Inc., Laurie Beth shows that there is no contradiction between earning a comfortable living & using your job to promote your deepest spiritual & personal beliefs. How exactly is this possible? To answer that question, Laurie Beth offers a wealth of stories gleaned from the Bible, anecdotes from her own life & consulting career, as well as tales from the best & the worst work situations in today's rapidly changing business environment. Jesus was the greatest spiritreneur the world has ever known. Motivated by His example, a new generation of spiritreneurs are transforming the world today. Filled with both inspiration & pragmatic advice, Jesus, Inc. is the clarion call & the instruction manual for everyone who wants to follow in His footsteps.
The launch : heeding the call to spiritreneurship -- The lurch : the early days and your new identity -- The lessons : learning through the wisdom and mistakes of others -- The love : living the visionary life of the spiritreneur.
Keywords: Management -- Religious aspects -- Christianity; Success in business; Jesus Christ -- Leadership; Executive ability -- Biblical teaching